Influence of postmortem injection of calcium chloride on tenderness of pork longissimus muscle - B J McFarlane; John A Unruh (Kansas Agricultural Experiment Station Research Reports, 1994)
Twenty-seven pork carcass sides were assigned randomly to either blast chilling for 1 h at -13°F followed by 23 h chill at 34°F or a standard chill at 34°F for 24 h. At 24 h postmortem, the longissimus muscle from the center loin region was removed and divided into anterior and posterior halves. Halves were assigned randomly to either calcium-chloride (CaCI2) injection or non-injected controls. Those receiving CaCl2 were injected with a .3 molar solution at 10% pump by weight. Muscles then were stored for 3 d at 34OF before 1-in chops were removed, cooked to an internal temperature of 160°F, and allowed to cool for 2 h before six .5 in cores were sheared. The Warner-Bratzler Shear (WBS) values were lower (more tender) for the CaCl2-injected loins than controls. Blast chilling decreased the combined purge and cooking losses compared to standard chilling. A second trial was conducted to determine the influence of only a 10% water injection on WBS and cooking loss. Five loins were divided into anterior and posterior halves and assigned randomly to either water injection or noninjected controls. Water injection did not influence either WBS or cooking loss values. In conclusion, 24 h postmortem injection of CaCl2 enhances the tenderness of pork longissimus muscle.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Pork; Calcium chloride; Tenderness